1989
DOI: 10.1128/jcm.27.10.2240-2244.1989
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic considerations and interpretation of microbiological findings for evaluation of chronic prostatitis

Abstract: Seventy-five patients attending a clinic for chronic prostatitis were evaluated by use of lower urinary tract localization cultures. Coagulase-negative staphylococci, alpha-hemolytic streptococci, and diphtheroids were the most common isolates, but none of these organisms were pathogens, based on the absence of bacteriuria or evidence of an inflammatory response in prostatic secretions. Recognized uropathogens were isolated in 12 (16%) of the 75 cases and included Escherichia coli in 6 cases, Enterococcus spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…The designation of CNS as pathogens in the etiology of chronic bacterial prostatitis is controversial (215,248,286). Nickel and Costerton (227), as well as several other earlier investigators (26,183,310), have presented evidence to suggest that S. epidermidis and S. saprophyticus can be associated with the clinical syndrome of chronic prostatitis and most likely are implicated in the pathogenesis of the prostatic inflammation. These CNS fulfilled the criteria of bacterial localization as set forth by Meares and Stamey (216), who compared CFU in expressed prostatic secretions and bladder urine.…”
Section: Specimen Collection and Processingmentioning
confidence: 96%
“…The designation of CNS as pathogens in the etiology of chronic bacterial prostatitis is controversial (215,248,286). Nickel and Costerton (227), as well as several other earlier investigators (26,183,310), have presented evidence to suggest that S. epidermidis and S. saprophyticus can be associated with the clinical syndrome of chronic prostatitis and most likely are implicated in the pathogenesis of the prostatic inflammation. These CNS fulfilled the criteria of bacterial localization as set forth by Meares and Stamey (216), who compared CFU in expressed prostatic secretions and bladder urine.…”
Section: Specimen Collection and Processingmentioning
confidence: 96%
“…By one estimate, half of all men suffer from symptoms of prostatitis at some point in their lives (54). Lower urinary tract localization studies represent the "gold standard" for diagnostic evaluation of chronic bacterial prostatitis (33,54). A lower urinary tract localization procedure involves a series of samples that includes first-void urine, midstream urine, expressed prostatic secretions, and postmassage urine specimens.…”
mentioning
confidence: 99%
“…The four-glass test has been used as a standard method of assessing prostatic inflammation and bacterial infection in the lower urinary tract in men with chronic prostatitis. [13][14][15] However, the four-glass tests can frequently show false negative results owing to prostatic duct obstruction, focal distribution of infection or inappropriate prostatic massage and false-positive results owing to microbial contamination. Furthermore, we found that the traditional four-glass test cannot accurately detect bacterial infection in the seminal vesicles.…”
Section: Discussionmentioning
confidence: 99%